ANALYSIS OF SURGICAL PATHOLOGY IN THE VETERINARY CLINIC “ASTI”, IN THE CITY OF KYIV - Kulynych, S. M.; Omelchenko, G. O.; Avramenko, N. O.; Bodnar, A. O. (Scientific Progress & Innovations, 2021)
A significant part of all diseases of small domestic animals are non-infectious, among which the most common are surgical, which in a large city make up to 50 %. The aim of the work was to determine the spreading of surgical pathology among small animals in the veterinary clinic “Asti” (Kyiv), to establish the probable etiological factors causing them and the characteristic symptom complex of the detected pathologies. The task of the research was: by conducting a surgical examination to establish the spread of surgical pathology among small animals and to reveal the causes of their occurrence, to characterize the symptoms and the main changes in the identified pathologies. The object of the study were small animals of different age and breeds with surgical pathology, which came to the veterinary clinic "Asti" for veterinary care during 2019–2020. During the monitoring examination based on the anamnesis taken from the owners, as well as the data of the clinical examination and, if necessary, special studies, the spreading, etiology, inherent symptoms and diagnosis were established. The obtained results were compared with the data in the literature, after which the final diagnosis was made. The article presents data on spreading of surgical pathology in small animals in the veterinary clinic "Asti", namely the etiological factors and symptoms. Analyzing our statistics on spreading the pathology in the veterinary clinic and routine manipulations, it was found that during the reporting period, clinically healthy cats were vaccinated, preventive dehelminthization, treatment against ectoparasites, nail trimming and grooming procedures were conducted, and 993 animals were treated. It was determined that the most common of the diagnosed pathology was surgical 56 %, and its structure was dominated by abscesses 10.8 %, neoplasia made 10.7 %, mammary gland tumors – 7.7 %, otitis externa – 7.0 %, dermatitis – 6.9 %, and wounds – 5.9 %. The development of surgical pathology was accompanied by the development of an inflammatory reaction and the corresponding pathological changes in soft tissues and bones in the area of the pathological process localization.